Mind : a brief introduction - Searle, John R. (Oxford, Oxford University Press, 2004)
"John Searle offers here a direct and open discussion of philosophy, one that skewers accepted wisdom even as it offers striking new insights into the nature of consciousness and the mind."--Jacket
Why I wrote this book -- A dozen problems in the philosophy of mind -- The turn to materialism -- Arguments against materialism -- Consciousness Part 1: Consciousness and the mind-body problem -- Consciousness Part II: The structure of consciousness and neurobiology -- Intentionality -- Mental causation -- Free will -- The unconscious and the explanation of behavior -- Perception -- The self -- Philosophy and the scientific world-view
Includes bibliographical references and index
Keywords: Philosophy of mind